Monty Python : a chronology, 1969-2012 - McCall, Douglas L., 1971- (Academic & Nonfiction Books anthology., 2013)
"A chronological listing of the members of the British comedy group Monty Python, both as a group and individually. Coverage spans between 1969 (the year Monty Python's Flying Circus debuted) and 2012. Entries include television, films, stage shows, books, records and interviews. Also included are an appendix of John Cleese's hilarious business-training films, indexes and selected bibliography"--